Environmental factors exert strong control over the climate-growth relationships of Picea abies in Central Europe - Altman, Jan; Fibich, Pavel; Santruckova, Hana; Dolezal, Jiri; Stepanek, Petr; Kopacek, Jiri; Hunova, Iva; Oulehle, Filip; Tumajer, Jan; Cienciala, Emil (The Science of the total environment, 2017)
The growth response of trees to changing climate is frequently discussed as increasing temperatures and more severe droughts become major risks for forest ecosystems. However, the ability of trees to cope with the changing climate and the effects of other environmental factors on climate-growth relationships are still poorly understood. There is thus an increasing need to understand the ability of individual trees to cope with changing climate in various environments. To improve the current understanding, a large tree-ring network covering the whole area of the Czech Republic (in 7×7km grids) was utilized to investigate how the climate-growth relationships of Norway spruce are affected by 1) various geographical variables, 2) changing levels of acidic deposition, 3) soil characteristics and 4) age, tree diameter and neighbourhood competition. The period from 1930 to 2013 was divided into four, 21-year long intervals of differing levels of acidic deposition, which peaked in the 1972-1993 period. Our individual-based, spatiotemporal, multivariate analyses revealed that spruce growth was mostly affected by drought and warm summers. Drought plays the most important negative role at lower altitudes, while the positive effect of higher temperature was identified for trees at higher altitudes. Increased levels of acidic deposition, together with geographical variables, were identified as the most important factors affecting climate-growth association. Tree age, tree size and soil characteristics also significantly modulate climate-growth relationships. The importance of all environmental variables on climate-growth relationships was suppressed by acidic deposition during periods when this was at a high level; growth was significantly more enhanced by spring and summer temperatures during these periods. Our results suggest that spruce will undergo significant growth reduction under the predicted climate changes, especially at the lower altitudes which lie outside of its natural range.
Keywords: období sucha; Tree rings; stromy; Droughts; Picea; časoprostorová analýza; Česká republika; Spatio-Temporal Analysis; Climate change; Trees; Czech Republic; půda; Climate; Divergence problem; Temperature; Altitude; podnebí; Individualistic approach; nadmořská výška; smrk; Soil; Air pollution; teplota